Genome-wide association study provides genetic insights into natural variation in watermelon rind thickness and single fruit weight - Gong, Chengsheng; Lu, Xuqiang; Zhu, Hongju; Anees, Muhammad; He, Nan; Liu, Wenge (Frontiers in Plant Science, 2022)
Rind thickness and fruit weight are agronomic traits closely related to quality and yield, which have attracted much attention from consumers and breeders. However, the genetic mechanism of these two traits is still not well understood in natural populations. In this study, rind thickness and single fruit weight in 151 watermelon accessions were determined in 2019 and 2020, and genome-wide association analysis was performed by integrating phenotypic and genotype data. Abundant phenotypic variation was found in the test population, and the watermelon with thinner rind thickness tended to have smaller fruit weights. Five significant SNPs were closely associated with rind thickness on chromosome 2 by Genome-wide association study (GWAS), i.e., 32344170, 32321308, 32304738, 32328501, and 32311192. And there were 21 genes were annotated in the candidate interval, most notably, Cla97C02G044160 belonged to the MADS family, and part of the genes in this family played an important role in regulating organ size, further analysis of gene structure, gene expression level, and phylogenetic tree showed that Cla97C02G044160 was a candidate gene for regulating target traits. In conclusion, our study provides molecular insights into the natural variation of watermelon rind thickness and single fruit weight, meanwhile, providing data support for molecular marker-assisted breeding.